Assessment of Adherence to Refills and Medication Self-Administer in Patients with Type 2 Diabetes Mellitus - Showaya, Ali Hasan; Kadhim, Alaa Jawad; Khachian, Alice (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To assess the Adherence to Refills and Medication Self-Administer in patients with type 2 diabetes. Methods: A descriptive study conducted among (110) patients with type 2 diabetic mellitus in Baghdad Teaching Hospital / Medical City Department, and Imam Ali Hospital / Al-Rusafa Health Department between October 10th to June 15th, 2023. A convenient (non-probability) sampling was used to achieve the objectives of the study. Adherence to Refills and Medication Self-Administer was assessed using Adherence to Refills and Medications Scale. Results: The results shown that the majority of the participants in the study were married women whose age ranges between (50 years) and above, with a primary education primary school graduate. The study found that patients, on average, refilled their medications less frequently than the recommended level (cut-off point of 16). The overall average score was 27.93, which is above the cut-off point. Conclusion: The study concludes that more than half of the sample did not adhere to refilling the medication for type 2 diabetes patient. Adherence to medications has a direct, one-way effect on patients with type 2 diabetes. Recommendations: The study encouraging guidance units to establish educational workshops and seminars for patients about diabetes medications and the importance of refilling and self-administering according to a daily schedule.